Non-sanctioning of illegal tackles in South African youth community rugby. Issue 6 (June 2018) - Brown, J.C.; Boucher, S.J.; Lambert, M.; Viljoen, W.; Readhead, C.; Hendricks, S.; Kraak, W.J.
Abstract: Objectives: The tackle event in rugby union ('rugby') contributes to the majority of players' injuries. Referees can reduce this risk by sanctioning dangerous tackles. A study in elite adult rugby suggests that referees only sanction a minority of illegal tackles. The aim of this study was to assess if this finding was similar in youth community rugby. Design: Observational study. Methods: Using EncodePro, 99 South African Rugby Union U18 Youth Week tournament matches were coded between 2011 and 2015. All tackles were coded by a researcher and an international referee to ensure that laws were interpreted correctly. The inter- and intra-rater reliabilities were 0.97–1.00. A regression analysis compared the non-sanctioned rates over time. Results: In total, 12 216 tackles were coded, of which less than 1% (n = 113) were 'illegal'. The majority of the 113 illegal tackles were front-on (75%), high tackles (72%) and occurred in the 2nd/4th quarters (29% each). Of the illegal tackles, only 59% were sanctioned. The proportions of illegal tackles and sanctioning of these illegal tackles to all tackles improved by 0.2% per year from 2011–2015 (p < 0.05). Conclusions: In these youth community rugby players, 59% of illegal tackles were not sanctioned appropriately. This was better than a previous study in elite adult rugby, where only 7% of illegal tackles were penalised. Moreover, the rates of illegal tackles and non-sanctioned illegal tackles both improved over time. However, it is critical that referees consistently enforce all laws to enhance injury prevention efforts. Further studies should investigate the reasons for non-sanctioning.